High Prevalence of ESBL-Producing Klebsiella pneumoniae Causing Community-Onset Infections in China - Zhang, Jing; Zhou, Kai; Zheng, Beiwen; Zhao, Lina; Shen, Ping; Ji, Jinru; Wei, Zeqing; Li, Lanjuan; Zhou, Jianying; Xiao, Yonghong (Frontiers in Microbiology, 2016)
The aim of this work was to investigate the epidemiological and genetic characteristics of ESBL-producing Klebsiella pneumoniae (ESBL-Kp) causing community-onset infections. K. pneumoniae isolates were collected from 31 Chinese secondary hospitals between August 2010 and August 2011. Genes encoding ESBL and AmpC beta-lactamases were detected by PCR. The isolates were assigned to sequence types (ST) using multi-locus sequence typing (MLST) and plasmid content was determined by PCR-based replicon typing. Eleven ESBL-Kp strains representing were selected to whole-genome sequencing (WGS) for investigating the genetic environment and plasmids encoding ESBL genes. A total of 578 K. pneumoniae isolates were collected, and 184 (31.8%) carried ESBL genes. The prevalence of ESBL-Kp varied from different geographical areas of China (10.2%-50.3%). The three most prevalent ESBL genes were blaCTX-M-14 (n=74), blaCTX-M-15 (n=60), and blaCTX-M-3 (n=40). MLST assigned 127 CTX-M-14 and CTX-M-15 producers to 54 STs, and CC17 was the most prevalent population (12.6%). STs (23, 37 and 86) that were known frequently associating with hypervirulent K. pneumoniae (hvKP) account for 14.1% (18/127). Phylogenetic analysis by concatenating the 7 loci of MLST revealed the existence of ESBL-producing K. quasipneumoniae (2 strains) and K. varricola (1 strain), which was further confirmed by WGS. IncFII type (n=130, 70.7%) was the predominant plasmid replicon. WGS analysis revealed various transmission mechanisms employed by different CTX-M genes. This study highlights the challenge of community-onset infections caused by ESBL-Kp in China. The prevalence of STs frequently associating with hvKP should be of concern. Surveillance of ESBL-KP causing community-onset infections now appears imperative.